2021
DOI: 10.21082/jtidp.v8n1.2021.p49-58
|View full text |Cite
|
Sign up to set email alerts
|

Patogen Penyakit Busuk Buah Kakao: Karakter dan Patogenisitas Phytophthora palmivora Isolat Asal Pakuwon, Sukabumi

Abstract: Phytophthora palmivora (Butl.)<em> is a major obstacle in cocoa cultivation worldwide. The study aimed to determine the morphological character and pathogenicity of P. palmivora Pakuwon isolate. The study was carried out from November 2020 to January 2021, which consisted of 3 activities e.g. (1) pathogen isolation, tests on growth rate and colony formation, and stimulation of sporangia, zoospore, and clamydospore formation, which was performed  in CMA, PDA, and mung bean media. The parameters observed w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
(16 reference statements)
0
1
0
Order By: Relevance
“…Furthermore, Phytophthora sp. fungus colonies exhibited relatively fast growth, ranging from 0.7 -0.8 cm per day, as noted by Wartono et al (2021). Microscopic analysis revealed that the fungi exhibit branched hyphae, produce ovoid sporangia resembling pears, and have round chlamydospores.…”
Section: Isolation and Identification Of Pathogenic Fungimentioning
confidence: 60%
“…Furthermore, Phytophthora sp. fungus colonies exhibited relatively fast growth, ranging from 0.7 -0.8 cm per day, as noted by Wartono et al (2021). Microscopic analysis revealed that the fungi exhibit branched hyphae, produce ovoid sporangia resembling pears, and have round chlamydospores.…”
Section: Isolation and Identification Of Pathogenic Fungimentioning
confidence: 60%